ANALISA PERBEDAAN BRAND IMAGE SITUS RITEL ONLINE LOKAL - Wicaksono, Kuspuji C. B. (Bina Nusantara University, 2014)
Information Technology development have provided an opportunity for all kind of company to sell their product for the customer directly from the display monitor. Each online retail shop has different brand image on the internet and they sell various kinds of product.This article is written to find out whether there are any differences on brand image for local online retail shop such as: www.lazada.co.id, www.blibli.co.id and www.mncshop.co.id based on six factors of brand image which are: benefits, attributes, cultures, values, personality and user. Data for the research were collected from questioners given to respondents who had seen and shopped at that local online retail shop mention above. Then each respondents were asked to gave scores based on the six factors of brand image for each online retail shop. Using the ANOVA method for testing the differences on brand images for each online retail shop. Result from the research revealed that there are a differences in brand image between www.lazada.co.id, www.blibli.co.id and www.mncshop.co.idfor beneftis, cultures and values, no differences on attributes, meanwhile personality cannot be tested. In this journal, the creator of online retail shop are expected to improve their brand image to distinguished one another differently.